Random diagonal codes for spectral amplitude coding optical CDMA systems using fiber Bragg-Grating - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org